PENGARUH TEMPERATUR QUENCH TERHADAP LAJU KOROSI DAN STRUKTUR MIKRO HASIL PENGELASAN BAJA KEYLOS 50 - Priatama, Arya Aji (Jurnal Nosel, 2014)
Medium carbon steels is a material commonly used in the industrial world, application of medium carbon steels often have problems that require welding to repair. Welding causes the corrosion resistance of a metal decreases, so that need for post- weld treated, one of the way with quenching. To get the quenching which has good corrosion resistance, need to know the media and the optimal temperature in the quenching process. In the process of quenching, cooling too quickly can cause the brittle nature of the increases thereby increasing the likelihood of cracking in the material which trigger corrosion. This study aims to: ( 1 ) determine the effect of temperature on the cooling medium flow rate of corrosion of steel welds keylos 50. ( 2 ) determine the effect of temperature on the cooling medium steel weld microstructure keylos 50. This research conducted in Inlastek Welding Institute for the welding process and DIII Mechanical Engineering Materials Laboratory UGM for corrosion testing process. The method used experimental method and the type of study is a quantitative study. The number of samples in this study were 4 pieces with 1 piece details without quenching and 3 samples experienced a variaton temperature of quenching media. Corrosion testing was conducted using a weight loss method with 3 pieces for each variation, plus 3 pieces of samples of raw materials , so the total samples for corrosion testing there are 15 pieces. Data analysis techniques in this study is a quantitative descriptive analysis techniques. The results of research have showed that the optimum quench temperature influence on the corrosion rate is quenching temperature is 25-30 ° C it was 273.876 mpy corrosion rate decreased by 15.95% compared with the raw material and the worst quench temperature is 5-10 ° C is 389.943 mpy or an increase of 19.67% compared with the raw material. However, the highest level of corrosion rate occurs in welds without treatment or quenching is 397.518 mpy corrosion rate increased by 21.99% compared with the raw material. These results are due to the air cooling quickly so having a micro structure that is dominated by accicular ferrite and ferrite side plate in weld metal region, then bainite and martensite in the HAZ region, while the water media cooling more slowly because of the heat welding is being held back by the water in a bucket.